2022
DOI: 10.1155/2022/7502185
|View full text |Cite|
|
Sign up to set email alerts
|

Watery Rose Apple: A Comprehensive Review of Its Traditional Uses, Nutritional Value, Phytochemistry, and Therapeutic Merits against Inflammation-Related Disorders

Abstract: The myrtle family, Myrtaceae, constitutes over 5500 species, and Syzygium is considered the largest genus of the flowering plants within the family. The watery rose apple, Syzygium aqueum, is a traditional medicinal plant with various bioactive compounds distributed in all plant parts. These include phenolic compounds, flavonoids, tannins, terpenoids, and essential oils. S. aqueum extracts and their isolated compounds showed multiple beneficial biological effects such as antibacterial, antifungal, antidiabetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 54 publications
1
5
0
Order By: Relevance
“…These findings agree with those reported from the Egyptian flora (Sobeh et al, 2018a). Also, other Syzygium species showed similar chemical patterns, among them Syzygium cumini, Syzygium samarangense, Syzygium aqueum; they are polyphenolsrich medicinal plants containing myricetin and gallic acid (Sobeh et al, 2018b;Chagas et al, 2018;Sobeh et al, 2018c;Gaspar et al, 2020;Yassir et al, 2022).…”
Section: Phytochemical Composition Of the Aqueous Extract Of S Jambos...supporting
confidence: 91%
“…These findings agree with those reported from the Egyptian flora (Sobeh et al, 2018a). Also, other Syzygium species showed similar chemical patterns, among them Syzygium cumini, Syzygium samarangense, Syzygium aqueum; they are polyphenolsrich medicinal plants containing myricetin and gallic acid (Sobeh et al, 2018b;Chagas et al, 2018;Sobeh et al, 2018c;Gaspar et al, 2020;Yassir et al, 2022).…”
Section: Phytochemical Composition Of the Aqueous Extract Of S Jambos...supporting
confidence: 91%
“…Recently, there has been a keen interest in identifying new plant-based antioxidants to protect the human body from free radical-related disorders such as diabetes, cancer, cardiovascular and neurodegenerative diseases, atherosclerosis, arthritis, asthma, anemia, inflammation, and so forth ( Pham-Huy et al, 2008 ; Yassir et al, 2022 ). Many research studies showed that various plant species contained significant amounts of polyphenolic compounds and flavonoids, which could also be applied as promising antioxidant agents in dietary supplements and as food additives to postpone or prevent rancidity.…”
Section: Biological Activities Of T Articulatamentioning
confidence: 99%
“…Several disorders and diseases are linked to the inflammatory responses including diabetes mellitus, rheumatoid arthritis, neurodegenerative diseases, and cancer ( 42 ). Many anti-inflammatory agents were isolated from plants such as curcumin, quercetin, capsaicin, resveratrol, and epigallocatechin-3-gallate ( 43 ).…”
Section: Biological and Pharmacological Activitiesmentioning
confidence: 99%